Intact perception of coherent motion, dynamic rigid form, and biological motion in chronic schizophrenia. (October 2018) - Keane, Brian P.; Peng, Yujia; Demmin, Docia; Silverstein, Steve M.; Lu, Hongjing
Highlights: Prior studies have shown poor biological motion perception in schizophrenia (SZ). To examine why, we had SZ patients and controls perform 3 types of motion tasks. Patients normally perceived coherent motion, dynamic form, and biological motion. Higher IQ was linked to better perception of dynamic form and biological motion. Stimulus differences or IQ or attention confounds may explain previous findings. Abstract: Background: Prior studies have documented biological motion perception deficits in schizophrenia, but it remains unclear whether the impairments arise from poor social cognition, perceptual organization, basic motion processing, or sustained attention/motivation. To address the issue, we had 24 chronic schizophrenia patients and 27 healthy controls perform three tasks: coherent motion, where subjects indicated whether a cloud of dots drifted leftward or rightward; dynamic rigid form, where subjects determined the tilt direction of a translating, point-light rectangle; and biological motion, where subjects judged whether a human point-light figure walked leftward or rightward. Task difficulty was staircase controlled and depended on the directional variability of the background dot motion. Catch trials were added to verify task attentiveness and engagement. Results: Patients and controls demonstrated similar performance thresholds and near-ceiling catch trial accuracy for each task (uncorrected p s > 0.1; d s < 0.35). In all but the coherent motion task, higher IQ correlated with better performance ( p s < 0.001). Conclusion: Schizophrenia patients have intact perception of motion coherence, dynamic rigid form, and biological motion at least for our sample and set-up. We speculate that previously documented biological motion perception deficits arose from task or stimulus differences or from group differences in IQ, attention, or motivation.